Hubungan Status Gizi Dengan Kejadian Dismenore Pada Remaja Putri Di SMP 2 Playen Gunung Kidul - Antika, Wanda Bayu (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Poor nutritional status in adolescent girls can result in pain during menstruation (dysmenorrhea). Dysmenorrhea itself is pain felt during menstruation which can interfere with the sufferer's daily activities. From the research results, it was reported that the incidence of dysmenorrhea was 79.1% in adolescents aged 13-14 years. The aim of this research was to determine the relationship between nutritional status and the occurrence of dysmenorrhea in adolescent girls at SMP 2 Playen Gunung Kidul. The research method used quantitative correlational with a population of 199 young women from grade 7 and grade 8 at SMP 2 Playen Gunung Kidul. The sample used in this research was 38 respondents from grade 7 and 28 respondents from grade 8 using a quota sampling technique. This data collection method uses questionnaires and observation of respondents' BMI values. This research analysis used an analytical survey (Spearman-Rho) with the results that there was no significant relationship between nutritional status and the incidence of dysmenorrhea with a P-value > 0.05 (0.993). However, in this study 43.3% of respondents had underweight nutritional status and 20.9% of respondents experienced frequent episodes of dysmenorrhea. The conclusion shows that the incidence of dysmenorrhea is not only influenced by nutritional status but is influenced by other factors. Future research is expected to examine the factors that influence dysmenorrhea.